Supramolecular assembly of cobaloxime on nanoring-coated carbon nanotubes: addressing the stability of the pyridine–cobalt linkage under hydrogen evolution turnover conditions. Issue 79 (12th September 2016) - Donck, Simon; Fize, Jennifer; Gravel, Edmond; Doris, Eric; Artero, Vincent
Abstract : A carbon nanotube–cobaloxime H2 -evolving nanohybrid catalyst was prepared through supramolecular assembly of tailored polymerizable amphiphiles, leading to the coordination of cobalt on pyridine-coated nanotubes. Abstract : A carbon nanotube–cobaloxime nanohybrid was prepared through supramolecular assembly of tailored polymerizable amphiphiles, leading to the coordination of cobalt on pyridine-coated nanotubes. This material was used as a catalyst for hydrogen evolution in fully aqueous media. This study provides a definitive asset regarding the stability of the pyridine–cobalt axial bond under H2 evolution turnover conditions.